Onychomycosis involving multiple nails in healthy infants - Uncommon but emerging fungal infection - Ajeet Kumar Negi; Sandhya Kumari; Ghanshyam Kumar Verma; Santwana Verma (Wolters Kluwer Medknow Publications, 2023)
Onychomycosis (OM) is common in adults but extremely rare in healthy infants. Here, we describe OM caused by Candida albicans and Trichophyton rubrum in two healthy and nonimmunocompromised infants. Multiple fingernails and toenails were involved in the form of onycholysis and yellowish discoloration in a 4-week-old neonate, whereas a 6-month-old infant presented with distal and lateral subungual type of OM. The diagnosis was established in both cases by the direct microscopic examination and fungal culture from nail scrapings. The infant with Candida OM responded to topical amorolfine with complete recovery within 3 months, while the case with T. rubrum OM was put on itraconazole pulse therapy for 3 months in the dosage of 5 mg/kg/day. We reported these cases for rarity of OM in infants, very young age of onset and multiple nail involvement in immunocompetent infants.